PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA YANG MENGALAMI KECELAKAAN MENURUT UNDANG-UNDANG NOMOR 13 TAHUN 2003 STUDI PADA UPTD BENIH INDUK PADI TANJUNG MORAWA DINAS KETAHANAN PANGAN, TANAMAN PANGAN DAN HORTIKULTURA PROVINSI SUMATERA UTARA - Ahyar, Muhammad; Falahiyati, Nurhimmi; Sahbudi, Sahbudi (Jurnal Sosial Humaniora Sigli, 2024)
The importance of labor protection is the main focus in an effort to ensure that every individual working in a company receives proper protection. In this context, the protection includes aspects of occupational health and safety, which aims to avoid the risk of accidents or injuries for workers. However, in reality, there are still violations of work protection provisions, such as the absence of personal protective equipment, which can threaten the safety of workers, especially at the Tanjung Morawa Rice Seed UPTD. In an effort to overcome these violations, this research carries out a descriptive method to describe the situation of legal protection against workers who experience accidents according to Law Number 13 of 2003 at the UPTD Induk Padi Tanjung Morawa. The results show that legal protection of workers is regulated in Article 6 of the Law, which contains the obligation of employers to provide rights and obligations to workers without discrimination. However, there are shortcomings in the details of the protection, especially regarding the protection of male workers. In addition, the protection of female workers is also stipulated in the Law, with a prohibition on female workers under the age of 18 to work during certain hours. Nevertheless, the implementation of legal protection of worker safety at the Tanjung Morawa Rice Seed UPTD still has challenges, where protection must include humanitarian and welfare aspects for workers.